1981
DOI: 10.1104/pp.68.4.835
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Distribution and Chemical Fate in Soybean Plants

Abstract: The distribution and chemical behavior of Cd2" in tissues and its chemical form in xylem water of soybean plants (cv. Williams) were investigated. FoDlowing root absorption, Cd is strongly retained by roots, with only 2% of the accumulated Cd being transported to leaves; as much as 8% was transported to seeds during seed filing. In vivo xylem exudates contained two anionic Cd complexes in addition to inorganic forms of Cd. Once accumulated in root and leaf tissues, Cd rapidly equilibrated between the insoluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(63 citation statements)
references
References 21 publications
9
53
0
1
Order By: Relevance
“…In the present study, it was found that Cd and Zn accumulated more in roots than in shoots. Similar results have been reported by several investigators in different species of plants 1,27,[31][32][33][34][35][36] . The differences in the ability of plants to accumulate heavy metals have been related to differences in their root morphology 37 .…”
Section: Scienceasia Scienceasia Scienceasiasupporting
confidence: 91%
“…In the present study, it was found that Cd and Zn accumulated more in roots than in shoots. Similar results have been reported by several investigators in different species of plants 1,27,[31][32][33][34][35][36] . The differences in the ability of plants to accumulate heavy metals have been related to differences in their root morphology 37 .…”
Section: Scienceasia Scienceasia Scienceasiasupporting
confidence: 91%
“…As stated by Heuillet et al (10) and Rauser and Ackerley (20) possible limitations of this method are leaching of loosely bound Cd during preparation of the tissue for electron microscopy and the possibility that the amount of Cd present in forms other than electron-dense granules might be too low to be detected by x-ray microanalysis. In contrast to electron microscopy studies, methods employing cell fractionation techniques (5,33) (14).…”
Section: Subcellular Localization Of Cdbps In Tobacco Leavesmentioning
confidence: 99%
“…Heavy metal concentrations were reported to be higher in roots in most studies (Cataldo et al, 1981;Rauser, 1987). Normally, Zn, Cd or Ni concentrations are 10 (or more) times higher in roots than those in shoots (Chaney et al, 1997).…”
Section: Heavy Metal Accumulation In Water Hyacinthmentioning
confidence: 97%